Comparison of the airway microbiota in children with chronic suppurative lung disease. Issue 1 (22nd December 2021) - Ahmed, Bushra; Cox, Michael J; Cuthbertson, Leah; James, Phillip; Gardner, Laura; Cookson, William; Davies, Jane; Moffatt, Miriam; Bush, Andrew
Abstract : Rationale: The airway microbiota is important in chronic suppurative lung diseases, such as primary ciliary dyskinesia (PCD) and cystic fibrosis (CF). This comparison has not previously been described but is important because difference between the two diseases may relate to the differing prognoses and lead to pathological insights and potentially, new treatments. Objectives: To compare the longitudinal development of the airway microbiota in children with PCD to that of CF and relate this to age and clinical status. Methods: Sixty-two age-matched children (age range 0.5–17 years) with PCD or CF (n=31 in each group) were recruited prospectively and followed for 1.1 years. Throat swabs or sputum as well as clinical information were collected at routine clinical appointments. 16S rRNA gene sequencing was performed. Measurements and main results: The microbiota was highly individual and more diverse in PCD and differed in community composition when compared with CF. While Streptococcus was the most abundant genus in both conditions, Pseudomonas was more abundant in CF with Haemophilus more abundant in PCD (Padj =0.0005). In PCD only, an inverse relationship was seen in the relative abundance of Streptococcus and Haemophilus with age. Conclusions: Bacterial community composition differs between children with PCD and those with CF. Pseudomonas is more prevalent in CF and Haemophilus in PCD, at least until infection with Pseudomonas supervenes. Interactions between organisms, particularly members of Haemophilus, Streptococcus and Pseudomonas genera appear important. Study of the interactions between these organisms may lead to new therapies or risk stratification.